2019
DOI: 10.1097/gme.0000000000001269
|View full text |Cite
|
Sign up to set email alerts
|

The experiences and needs of Asian women experiencing menopausal symptoms: a meta-synthesis

Abstract: Objective: The aim of the study was to explore the experiences and needs of Asian women who were experiencing or had experienced menopause and to determine possible differences in experiences due to acculturation by comparing Asian women living in Asia and those living in Western countries. Methods: Six electronic databases were systematically searched: PubMed, CINAHL, Embase, Scopus, PsycINFO, and ProQuest. The search resulted in 17 qualitative studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 52 publications
0
31
0
Order By: Relevance
“…Although similar in terms of sociodemographic characteristics, we believe that the results are different because the studies were conducted in different regions. Studies show that large differences both between and within cultures are influential in the perception of menopause, in terms of the menopausal behaviors and complaints in this period [27, 28]. Therefore, to ensure the healthy well-being of postmenopausal women, the implementation of culturally appropriate mitigation and management strategies is necessary [28].…”
Section: Discussionmentioning
confidence: 99%
“…Although similar in terms of sociodemographic characteristics, we believe that the results are different because the studies were conducted in different regions. Studies show that large differences both between and within cultures are influential in the perception of menopause, in terms of the menopausal behaviors and complaints in this period [27, 28]. Therefore, to ensure the healthy well-being of postmenopausal women, the implementation of culturally appropriate mitigation and management strategies is necessary [28].…”
Section: Discussionmentioning
confidence: 99%
“…Studies show large differences between cultures, in sociodemographic and other determinants of GSM 21,22 . In the present study, GSM was more in patients with low socioeconomic status (OR= 1.40, P= 0.295551) and significantly associated with lower educational level (OR= 2.07, P= 0.026647) (table 4).…”
Section: Resultsmentioning
confidence: 99%
“…An insignificant intervention effect was found in the meta‐analysis on hot flashes, which is contrary to the findings of a previous review (Woods et al, ) and a study (Avis, Legault, Russell, Weaver, & Danhauer, ) on MBTs that found significant effects on reducing hot flashes among Western and Asian perimenopausal and menopausal women. Western and Asian perimenopausal women have different menopausal symptoms, experiences, and needs (Shorey & Ng, ). It was reported that Asian perimenopausal women experienced lesser frequencies of hot flashes but more episodes of sleeplessness (Baber, ) compared with Western perimenopausal women.…”
Section: Discussionmentioning
confidence: 99%
“…However, a previous review on exercise for alleviating vasomotor menopausal symptoms noted insufficient evidence to suggest that exercise is an effective treatment for menopausal symptoms when compared with hormone therapy and yoga due to the lack of trials (Daley, An insignificant intervention effect was found in the meta-analysis on hot flashes, which is contrary to the findings of a previous review (Woods et al, 2014) and a study (Avis, Legault, Russell, Weaver, & Danhauer, 2014) on MBTs that found significant effects on reducing hot flashes among Western and Asian perimenopausal and menopausal women. Western and Asian perimenopausal women have different menopausal symptoms, experiences, and needs (Shorey & Ng, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation